Maulana Abul Kalam Azad A Great Educational Pioneer - Peerzada, Najmah (JOURNAL OF INDIAN EDUCATION, 2013)
Maulana Abul Kalam Azad was a great intellectual, scholar and philosopher. He was one of the prominent freedom fighters of India, president of Indian National Congress and the first education minister of free India. Maulana Azad erected his educational philosophy on the basis of his vast and thorough knowledge of Islam and the concepts of both the East and the West. He approached education in a manner which was relevant and suitable to man as the supreme creation among all creatures on the earth. He visualised such an educational system which could help in bringing readjustment among different outlooks and ideas. He proposed scientific and technological outlook in educational system, so as to deal with the present situation, not only at the national level, but also to compete at the international level. In his involvement with education as a mission of guiding mankind towards higher goals of life, he provided, over a period of half a century, a kind of educational leadership, which the present study seeks to examine in depth.